2021
DOI: 10.1038/s41598-021-95499-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo exploration of synaptic projections in frontotemporal dementia

Abstract: The purpose of this exploratory research is to provide data on synaptopathy in the behavioral variant of frontotemporal dementia (bvFTD). Twelve patients with probable bvFTD were compared to 12 control participants and 12 patients with Alzheimer’s disease (AD). Loss of synaptic projections was assessed with [18F]UCBH-PET. Total distribution volume was obtained with Logan method using carotid artery derived input function. Neuroimages were analyzed with SPM12. Verbal fluency, episodic memory and awareness of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…Unbiased proteomic analysis of frontal cortical tissues from postmortem tissues of FTLD-FUS and controls showed altered expression of proteins associated with synaptic communication (syntaxin subunits: STX1A, STX1B, and STXBP1, synapsin 3: SYN3, synaptotagmin I: SYT1) and those involved in cellular transport pathways (clathrin-associated adaptor proteins: AP1B1, AP2A1, AP2A2, AP2B1) (Martins-De-Souza et al, 2012 ). These findings were consistent with previously discussed changes in synaptic connectivity observed in FTLD and ALS (Henstridge et al, 2018 ; Malpetti et al, 2021 ; Salmon et al, 2021 ). Additionally, FTLD-FUS tissues had significant changes in proteins involved in signaling pathways (calcium-related proteins, CAMK2A, protein phosphatase 3, catalytic subunit, alpha isozyme: PPP3CA and neurochondrin: NCDN) (Martins-De-Souza et al, 2012 ).…”
Section: Als/ftd Models Of Diseasesupporting
confidence: 93%
See 1 more Smart Citation
“…Unbiased proteomic analysis of frontal cortical tissues from postmortem tissues of FTLD-FUS and controls showed altered expression of proteins associated with synaptic communication (syntaxin subunits: STX1A, STX1B, and STXBP1, synapsin 3: SYN3, synaptotagmin I: SYT1) and those involved in cellular transport pathways (clathrin-associated adaptor proteins: AP1B1, AP2A1, AP2A2, AP2B1) (Martins-De-Souza et al, 2012 ). These findings were consistent with previously discussed changes in synaptic connectivity observed in FTLD and ALS (Henstridge et al, 2018 ; Malpetti et al, 2021 ; Salmon et al, 2021 ). Additionally, FTLD-FUS tissues had significant changes in proteins involved in signaling pathways (calcium-related proteins, CAMK2A, protein phosphatase 3, catalytic subunit, alpha isozyme: PPP3CA and neurochondrin: NCDN) (Martins-De-Souza et al, 2012 ).…”
Section: Als/ftd Models Of Diseasesupporting
confidence: 93%
“…Recent imaging techniques have been developed to study synaptic density in living FTD patients and support these histological findings. The use of [11C]UCB-J PET, a radio-ligand that selectively binds to synaptic vesicle protein 2A (SV2A), to assess the regional distribution of synaptic loss in patients with probable bvFTD and carriers of C9ORF72 hexanucleotide repeat expansions, showed that loss of synaptic densities occur in the frontotemporal region (Malpetti et al, 2021 ; Salmon et al, 2021 ). Importantly, this study showed that pre-symptomatic FTD-C9 patients had reduced synaptic density and that extensive synaptic loss was observed in patients with severe cognitive impairments (Malpetti et al, 2021 ).…”
Section: Neuropathological Features Of Als and Ftdmentioning
confidence: 99%
“…[ 18 F]UCB-H uptake was assessed in patients with a behavioral variant of frontotemporal dementia, showing a trend toward a decrease in the distribution volume of the tracer in the right parahippocampal region compared to healthy subjects. Comparisons between patients with the behavioral variant of frontotemporal dementia and data from a group of patients with Alzheimer’s disease did not result in significant differences ( Salmon et al, 2021 ).…”
Section: Synaptic Vesicle Glycoprotein 2a and Positron Emission Tomog...mentioning
confidence: 99%
“…[ 11 C]UCB-J is not the only potential marker of synaptic health in frontotemporal dementia, and related disorders. A previous study using [ 18 F]UCB-H PET to assess synaptic loss did not identify a deficit in frontotemporal dementia vs controls, nor was there a difference between frontotemporal dementia and Alzheimer’s disease (Salmon et al ., 2021). The lower specific binding of [ 18 F]UCB-H compared to [ 11 C]UCB-J may have contributed to the null result.…”
Section: Discussionmentioning
confidence: 98%